2008
DOI: 10.1111/j.1572-0241.2008.01828.x
|View full text |Cite
|
Sign up to set email alerts
|

An Open Label, Pilot, Randomized Controlled Trial of NoradrenalineVersusTerlipressin in the Treatment of Type 1 Hepatorenal Syndrome and Predictors of Response

Abstract: Noradrenaline may be an effective and safe alternative to terlipressin in improving renal functions. Various baseline parameters and DCD4 can be used to predict response to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
232
1
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(248 citation statements)
references
References 23 publications
9
232
1
6
Order By: Relevance
“…Our observations regarding factors predictive of HRS reversal and survival essentially confirm what has been observed in previous studies,22, 23, 24, 25, 26, 27 with the exception of the absence of a precipitating cause for HRS‐1, absence of prior rifaximin use in the terlipressin group, and male sex in the placebo group – all new observations. The absence of prior rifaximin use as a factor predictive of HRS reversal in the terlipressin group is of interest; it is possible that patients without prior rifaximin exposure are less ill than those receiving rifaximin.…”
Section: Discussionsupporting
confidence: 89%
“…Our observations regarding factors predictive of HRS reversal and survival essentially confirm what has been observed in previous studies,22, 23, 24, 25, 26, 27 with the exception of the absence of a precipitating cause for HRS‐1, absence of prior rifaximin use in the terlipressin group, and male sex in the placebo group – all new observations. The absence of prior rifaximin use as a factor predictive of HRS reversal in the terlipressin group is of interest; it is possible that patients without prior rifaximin exposure are less ill than those receiving rifaximin.…”
Section: Discussionsupporting
confidence: 89%
“…In small comparative studies, norepinephrine has demonstrated a similar rate of HRS reversal and patient survival when compared with terlipressin [28,29]. Adverse effects between norepinephrine and terlipressin are similar, with reversible cardiac and digital ischemia being the most common adverse events [29]. The cost of norepinephrine therapy is also significantly lower than terlipressin (107 ± 31 versus 1536 ± 40 Euros, P < 0.0001), making it an attractive alternative therapy [28].…”
Section: Norepinephrine Versus Terlipressinmentioning
confidence: 91%
“…Similar to terlipressin, in patients with HRS, norepinephrine effectively improves UOP, sodium excretion, serum sodium concentration, creatinine clearance (CrCl), MAP, plasma renin activity, and aldosterone activity. In small comparative studies, norepinephrine has demonstrated a similar rate of HRS reversal and patient survival when compared with terlipressin [28,29]. Adverse effects between norepinephrine and terlipressin are similar, with reversible cardiac and digital ischemia being the most common adverse events [29].…”
Section: Norepinephrine Versus Terlipressinmentioning
confidence: 96%
“…Alpha-adrenergic agonists, such as norepinephrine [Sharma et al 2008;Singh et al 2012] or midodrine, in combination with octreotide and albumin [Angeli et al 1999;Skagen et al 2009;Wong et al 2004], are a reasonable alternative to terlipressin because of their low cost and wide availability. However, data on their use are limited.…”
Section: Albuminmentioning
confidence: 99%